Search for a W′ boson decaying to a τ lepton and a neutrino in proton-proton collisions at vs=13TeV; Physics Letters B; Vol. 792 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen